A Pragma-Dialectical Study of Personal Attack in China-Related Letters to the Editorof The New York Times - Pinchao, Lu (Sinología hispánica. China Studies Review, 2016)
This article under the research framework of pragma-dialectics, analyses the use of personal attacks in the China-related Letters to the Editor of The New York Times, and evaluates its reasonableness. The research results show that the personal attacks in the China-related Letters to the Editor of The New York Times can be mainly classified into three subtypes: the abusive variant (insult others), the circumstantial variant (suspect motives) and the tu quoque (you also). Both reasonable and unreasonable use of personal attack are identified. The unreasonable use of personal attack is mainly caused by: (1) the use of personal attack prevents the opponents from casting doubts or proposing his or her standpoint; (2) the use of personal attack has deficiency or even is invalid in logic, failing in the examination of critical questions. On account of this, the related discourse subjects in similar kind of discourse practice, should: (1) design their arguments reasonably according to the code of conduct of critical discussion (Ten Commandments); (2) consider the audience as an extremely rigor one, making sure that the argument can pass any critical examination, and so the rational and responsible figure of the proponents can be guaranteed.